Discourses of hijab in post-Soviet Kazakhstan: historical and modern aspects - Mingisheva, N. (Ye.A.Buketov Karaganda State University Publ., 2014)
My paper is focused on some comparative analysis of Western and Islamic feminist interpretations of hijab and their application to post-Soviet discourse on the hijab in present-days Kazakhstan. During recent years there are diverse forms of hijab wearing in the country from totally covering of a female body to some open «Arab style» of the hijab. In the same time, after extremist attacks in the Western and Southern Kazakhstan, the situation with the hijab is changed to the idea of traditional («Kazakh») Islam when the hijab is not preferred with the power discourse. My main research questions for my paper are following: What interpretations about hijab in the Western and Islamic narratives are applied to the Kazakhstan’s case? How the hijab discourse is constructed in post-Soviet Kazakhstan? What is the meaning of hijab after «atheism era» in the Central Asian country where majority is Muslims? What attitudes are between secular and religious discourses according to the hijab in Kazakhstan now? What hijab means for secular majority and young Muslims? What young Muslim men and women speak about hijab? My research is based on interviews of two males and two females who identify themselves as Muslims.
Посткеңестік Қазақстандағы хиджаб дискурстары: тарихи жəне қазіргі аспектілері
Дискурсы хиджаба в постсоветском Казахстане: исторические и современные аспекты
Keywords: hijab; Islam; colonialism; postcolonialism; Islamic feminism; secularism; traditional Islam; discourse; narrative; Kazakhstan